Investment vs debt trade-offs in the post-COVID-19 European economy - Laurent Maurin; Rozália Pál (European Investment Bank (EIB), 2020)
We use firm-level financial data to illustrate the impact of the COVID-19 crisis under several scenarios. We estimate COVID-19 induced cumulative net revenue losses for EU companies in the range of 5.4 to 10.0% of total assets, depending on the strength of the policy support and length of the normalisation period. The results appear robust to the consideration of sector specific decline in sales and cost-elasticities. The decline in internal financing capacity is likely to reduce investment by 24.3 to 48.5% during the COVID-19 crisis, compared to 19% during the Great Financial Crisis (GFC). Using historical regularities, we then assess the likelihood of such decline by estimating a macro based Bayesian VAR model for which we identify a standard demand shock. We then calibrate the demand shock to generate the computed decline in net revenues associated to the most benign scenario. The comparison between conditional and unconditional projections supports the existence of a tradeoff faced by corporates between investment and leverage. It also suggests that, should the estimated gap in net revenues materialise as the result of the crisis, the decline in corporate investment would likely be within the computed ranges.
Keywords: E22; D92; F34; G31; G32; 330; Corporate investment; leverage; financing structure; firm-level data; Scenarios; calibration; BVAR models; shocks identification; conditional projections